2003
DOI: 10.1046/j.1365-246x.2003.01923.x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetic study of the El Quemado complex and Marifil formation, Patagonian Jurassic igneous province, Argentina

Abstract: SUMMARY The upper Jurassic El Quemado Complex was sampled at 36 sites from five localities in the cordilleran foothills of southern Patagonia between Lago Argentino and Lago Posadas–Sierra Colorada, and the middle Jurassic Marifil Formation at 12 sites in the Somuncurá Massif near Camarones. The main lithology was ignimbrite, with minor tuff and lava. Petrographical and SEM observation show that the El Quemado rocks suffered an intense, high‐temperature alteration which resulted in transformation of most prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 48 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…The El Quemado igneous pole from Patagonia (South America), dated at 156.5 ± 1.9 Ma on the basis of 40 Ar/ 39 Ar analyses on one partially altered sample [ Iglesia Llanos et al ., ] and included in the 160 Ma mean pole of K&I, indeed plots with the constituents of that mean pole, for example, the 169 Ma Moat volcanics pole, rather than near either the Triple B or Peddie poles of ostensibly more similar ages (Figure ). The El Quemado Formation could be a few million years older with updated monitor standards [ Kuiper et al ., ], it may have suffered a relatively minor yet crucial resetting of its geochronological clock, or its magnetic directions were affected by local tectonic rotations [ Rapalini , ], emphasizing the tight age and structural control needed to resolve events during such an interval of rapid polar shift.…”
Section: Interpretation Of Jurassic Polar Wandermentioning
confidence: 90%
See 2 more Smart Citations
“…The El Quemado igneous pole from Patagonia (South America), dated at 156.5 ± 1.9 Ma on the basis of 40 Ar/ 39 Ar analyses on one partially altered sample [ Iglesia Llanos et al ., ] and included in the 160 Ma mean pole of K&I, indeed plots with the constituents of that mean pole, for example, the 169 Ma Moat volcanics pole, rather than near either the Triple B or Peddie poles of ostensibly more similar ages (Figure ). The El Quemado Formation could be a few million years older with updated monitor standards [ Kuiper et al ., ], it may have suffered a relatively minor yet crucial resetting of its geochronological clock, or its magnetic directions were affected by local tectonic rotations [ Rapalini , ], emphasizing the tight age and structural control needed to resolve events during such an interval of rapid polar shift.…”
Section: Interpretation Of Jurassic Polar Wandermentioning
confidence: 90%
“…Also shown for reference are the accepted poles from North America nearest in age to the Triple B and Peddie kimberlite poles from the 169 Ma Moat volcanics [ Van Fossen and Kent , ] and the 146 Ma Ithaca kimberlite [ Van Fossen and Kent , ], which are included in the 160 and 145 Ma mean poles, respectively, that bracket the monster polar shift (dashed line). The pole from the El Quemado Formation of Patagonia [ Iglesia Llanos et al ., ] plots in North American coordinates (labeled EQ: 84.4°N 122.5°E) near the older end of the polar shift, suggesting that its age is somewhat older than cited (156.5 ± 1.9 Ma) or its direction may have been biased by local tectonic rotations [ Rapalini , ].…”
Section: Interpretation Of Jurassic Polar Wandermentioning
confidence: 99%
See 1 more Smart Citation
“…From elsewhere in South America, we exclude a venerable result for the Mendoza lavas from South Nihuil, Argentina [ Creer et al , 1970], their reported age (Triassic or Permian) being poorly constrained. On the other hand, comprehensive isotopic dating shows that the silicic volcanics of the Marifil Formation in Patagonia are essentially coeval with the Karroo‐Ferrar‐Tasmanian magmatic province at ∼183 Ma [ Pankhurst et al , 2000]; accordingly its pole [ Iglesia Llanos et al , 2003] is assigned that age. Although the Lepa and Osta Arena formations of Patagonia [ Vizán , 1998] are biostratigraphically dated as late Pliensbachian‐early Toarcian, and may therefore also belong to this magmatic province, we have listed the result separately.…”
Section: Selection Of Cratonic Polesmentioning
confidence: 99%
“…Although the Lepa and Osta Arena formations of Patagonia [ Vizán , 1998] are biostratigraphically dated as late Pliensbachian‐early Toarcian, and may therefore also belong to this magmatic province, we have listed the result separately. Finally, we include poles for the 167 Ma Chon Aike Formation of Patagonia, summarized from the literature by Vizán [998], and for the 156.5 Ma El Quemado Formation of Patagonia [ Iglesia Llanos et al , 2003]. …”
Section: Selection Of Cratonic Polesmentioning
confidence: 99%